We may dominate the world : ambition, anxiety, and the rise of the American Colossus - Mirski, Sean A. (PublicAffairs, 2023)
"Sean A. Mirski tells the story of how the United States became a regional hegemon in the century following the Civil War. By turns reluctant and ruthless, the U.S. squeezed their European rivals out of the hemisphere while landing forces on their neighbors' soil with dizzying frequency. Mirski reveals the reasons behind this muscular foreign policy in a narrative full of twists, colorful characters, and original accounts of the palace coups and bloody interventions that turned the fledgling republic into a global superpower"--